Pengaruh Struktur Modal, Kepemilikan Manajerial, Dan Kinerja Keuangan Terhadap Nilai Perusahaan - Antari, Dewa Ayu Prati Praidy; DANA, I MADE (E-Jurnal Manajemen; Vol 2 No 3 (2013), 2013)
To determine capital structure effect, insider ownership and finance performance to the firm value on manufacture companies which is listed in Indonesian Stock Exchange period 2005-2010, either simultan or parsial, is aimed for this research. Purposive sampling was choosen as the methode in determining samples and in solving problems that appears in this research regression analysis with alfa (?) signification level = 5% was used. The result of this statistic research showed that capital structure has negative effect but not significant to the firm value, insider ownership has negative and significant effect to the firm value, while finance performance has positive and significant effect to the firm value. Keyword: capital structure, insider ownership, finance performance and firm value